2021
DOI: 10.1158/2159-8290.cd-20-1325
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Taxonomy of Tumor Suppression in Oncogenic KRAS–Driven Lung Cancer

Abstract: Cancer genotyping has identified a large number of putative tumor suppressor genes. Carcinogenesis is a multistep process, but the importance and specific roles of many of these genes during tumor initiation, growth, and progression remain unknown. Here we use a multiplexed mouse model of oncogenic KRAS–driven lung cancer to quantify the impact of 48 known and putative tumor suppressor genes on diverse aspects of carcinogenesis at an unprecedented scale and resolution. We uncover many previously understudied f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 81 publications
1
68
2
Order By: Relevance
“…However, we found that there were more important mechanisms of ISM1 in CRC that have not been reported. In the GSEA results, enriched pathways, such as the EMT, hypoxia, KRAS signaling, angiogenesis, Notch and Hedgehog signaling pathways, were significantly positively associated with ISM1, and most of these pathways are vital to cell proliferation, migration and resistance in cancer ( Wang et al, 2020 ; Andrysik et al, 2021 ; Cai et al, 2021 ), including CRC. We exclusively focused on the EMT signaling pathway because 71% of genes in the pathway exhibited a significantly positive correlation with ISM1.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that there were more important mechanisms of ISM1 in CRC that have not been reported. In the GSEA results, enriched pathways, such as the EMT, hypoxia, KRAS signaling, angiogenesis, Notch and Hedgehog signaling pathways, were significantly positively associated with ISM1, and most of these pathways are vital to cell proliferation, migration and resistance in cancer ( Wang et al, 2020 ; Andrysik et al, 2021 ; Cai et al, 2021 ), including CRC. We exclusively focused on the EMT signaling pathway because 71% of genes in the pathway exhibited a significantly positive correlation with ISM1.…”
Section: Discussionmentioning
confidence: 99%
“…The previous study did not explore the causes of poor survival and prognosis in the high-risk group. In our study, the relationship with immune infiltration was found in the high-risk group to be mainly enriched in genes upregulated in response to hypoxia [ 50 52 ], TNF [ 53 , 54 ], EMT [ 55 , 56 ], wound healing, fibrosis, metastasis, and KRAS activation [ 57 , 58 ]. These pathways are closely related to tumorigenesis, invasion, and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Given the widespread genetic and epigenetic alterations in human tumors, genomic analyses have limited ability to delineate causal relationships between genomic alterations and tumor development [1]. To determine whether combinatorial tumor suppressor gene inactivation can drive lung tumor initiation in the absence of oncogene activation, we coupled Cre/loxP-based genetically engineered mouse models and somatic CRISPR/Cas9-based genome editing with tumor barcoding and high-throughput barcode sequencing (Tuba-seq) [31][32][33][34][35]. We used Cre/loxP to inactivate each of five "core" tumor suppressor genes (Trp53, Lkb1/Stk11, Keap1, Nf1, and Pten).…”
Section: Combinatorial Tumor Suppressor Gene Inactivation Enables Lung Tumor Developmentmentioning
confidence: 99%
“…We used Cre/loxP to inactivate each of five "core" tumor suppressor genes (Trp53, Lkb1/Stk11, Keap1, Nf1, and Pten). These genes operate within diverse pathways and are frequently inactivated in human lung cancers, including oncogene-negative lung adenocarcinomas (Figure S2a-b) [35][36][37][38]. We used CRISPR/Cas9 to coincidentally inactivate panels of additional tumor suppressor genes in lung epithelial cells in mice with floxed alleles of each of the "core" tumor suppressors, a Cre-reporter allele (R26 LSL-Tom (T) [36]), and a Cre-regulated Cas9 allele (H11 LSL-Cas9 (C) [37]).…”
Section: Combinatorial Tumor Suppressor Gene Inactivation Enables Lung Tumor Developmentmentioning
confidence: 99%